THE INFLUENCE OF BRAND TRUST AND PRICES ON PRENDJAK TEA BAG PURCHASE DECISION (Case Study of Liza Department Store Bangkinang City) - Rinaldi Rinaldi; Zulher Zulher; Litra Diantara (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the effect of Brand Trust and price on purchasing decisions, the analysis used in this study is multiple linear analysis. The population in this study is all consumers, totaling 96 people at Liza Toserba Bangkinang City. unknown population. Data collection techniques used are questionnaires, research files and interviews. Hypothesis testing was carried out with the F test and t test. Based on the results of the study, it can be concluded that simultaneously Brand Trust and Price affect purchasing decisions, while the partial test of Brand Trust has an effect on purchasing decisions, the close relationship between the independent variables and the dependent variable is very strong with the contribution the independent variable to the dependent variable is 63.5%. The results of this analysis indicate that Brand Trust and Price have a significant simultaneous and partial effect on purchasing decisions for The Celup Prendjak Case Study of Liza Department Store Bangkinang City.